2017
DOI: 10.1002/fuce.201700031
|View full text |Cite
|
Sign up to set email alerts
|

SOFC Operation with Real Biogas

Abstract: Biogas is a valuable energy source and will be available in future in systems relying on renewables. It is an attractive fuel for solid oxide fuel cells (SOFC), which are able to utilize the carbon contained in the biogas and which produce electricity with high efficiency. In the current paper, state‐of‐the‐art SOFCs were studied regarding performance and durability in relation to biogas as fuel and considering important contaminants, specifically sulfur. First, the catalytic behavior in relevant synthetic bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…This finding was confirmed at SOFC cell level in the presence of sulphur impurities and typical biogas compositions [35]. The observed degradation of the power output under steam reforming conditions was even stopped when using CO2 as reforming agent instead of steam [15].…”
Section: Biogasmentioning
confidence: 60%
See 2 more Smart Citations
“…This finding was confirmed at SOFC cell level in the presence of sulphur impurities and typical biogas compositions [35]. The observed degradation of the power output under steam reforming conditions was even stopped when using CO2 as reforming agent instead of steam [15].…”
Section: Biogasmentioning
confidence: 60%
“…Catalytic studies on SoA anodes indicated that the presence of CO2 can mitigate the sulphur poisoning effect on the methane reforming reaction [34]. This finding was confirmed at SOFC cell level in the presence of sulphur impurities and typical biogas compositions [35]. The observed degradation of the power output under steam reforming conditions was even stopped when using CO2 as reforming agent instead of steam [15].…”
Section: Biogasmentioning
confidence: 77%
See 1 more Smart Citation
“…Pairing this abundant and under-utilized fuel with SOFC with higher efficiency would increase the generated electricity while considerably reducing the carbon footprint of energy services. In addition, studies by Johnson et al [35] and Hagen et al [36] show that the presence of CO2 (instead of pure methane) in biogas can suppress the effect of sulphur poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Power output during single cell SOFC test with real biogas from a landfill unit (bottle 1-3 with gas cleaning, bottle 4 without gas cleaning) and an intermediate period using synthetically mixed biogas under dry reforming conditions at 750 o C, from ref (15). …”
mentioning
confidence: 99%